Analysis of The Effect of Inflation, GRDP, Total Population and HDI on The Rate of Open Unemployment in Four Cities in The Province of North Sumatra - Berkat Juni Krisman Gulo; Sirojuzilam Sirojuzilam; Irsad Lubis (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Study This aim for test and analyze influence inflation, GRDP, total population, and HDI against level unemployment open at four cities in North Sumatra Province. The type of data used in study is quantitative data types with secondary data. The object in study is four cities in North Sumatra Province. Study This using panel data (Pooled Data). combines Time Series and Cross Section data for 16 years that is start from 2005-2020. Variables used are inflation, GRDP, Total Population and HDI. Method analysis in study This use Fixed Effect Model (FEM), using E-views 10 as tool estimate. Regression results show that Inflation influential negative and no significant to the Open Unemployment Rate, GRDP has an effect negative and significant to the Open Unemployment Rate, Total Resident influential positive and significant effect on the Open Unemployment Rate and HDI negative and no significant to the Open Unemployment Rate. Then exists a connection between Inflation, GRDP, Total Population and HDI with an Open Unemployment Rate of 62.19%. the rest of 37.81% explained by variables others who don't enter into models.